TNF-α in Uveitis: From Bench to Clinic - Jiang, Qi; Li, Zhaohuai; Tao, Tianyu; Duan, Runping; Wang, Xianggui; Su, Wenru (Frontiers in Pharmacology, 2021)
Uveitis is an inflammation of the iris, ciliary body, vitreous, retina, or choroid, which has been shown to be the first manifestation of numerous systemic diseases. Studies about the immunopathogenesis and treatment of uveitis are helpful to comprehend systemic autoimmune diseases, and delay the progression of systemic autoimmune diseases, respectively. Tumor necrosis factor-alpha (TNF-α), a pleiotropic cytokine, plays a pivotal role in intraocular inflammation based on experimental and clinical data. Evidence of the feasibility of using anti-TNF-α agents for uveitis management has increased. Although there are numerous studies on TNF-α in various autoimmune diseases, the pathological mechanism and research progress of TNF-α in uveitis have not been reviewed. Therefore, the objective of this review is to provide a background on the role of TNF-α in the immunopathogenesis of uveitis, as well as from bench to clinical research progress, to better guide TNF-α-based therapeutics for uveitis.